INTERDEPENDENCE OF FOREIGN AID AND MACRO-ECONOMIC VARIABLES IN PAKISTAN - Muhammad Yasir Nadeem , Touqeer Abbas , Rana Khalid Mehmood (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The study investigated the impact of foreign aid on macroeconomic variables by using time series data for the period 1988-2013 in Pakistan. Various time series properties were tested like Augmented Dickey-fuller test for stationary, Akaike information criterion test for lag length and Johansen co-integration test to check the long run relationship between variables and found three co-integrating vectors in the long run. Vector Error correction term showed a high speed of adjustment towards equilibrium in the short-run. The public expenditure and unemployment results were significant whereas the poverty variable found insignificant. Foreign aid may be helpful under the effective fiscal, monetary, and trade policies. Therefore, it is recommended that the government and donors should improve the co-ordination for better outcomes to their aid projects by concentrating on conditional aid.